Discretionary Authority in Government Administration after Law Number 30 of 2014 concerning Government Administration - Judijanto, Loso; Hildawati, Hildawati (West Science Law and Human Rights, 2025)
This study examines the regulation and implementation of discretionary authority in Indonesian government administration following the enactment of Law Number 30 of 2014 concerning Government Administration. Using a normative juridical approach, the research analyzes the legal framework, guiding principles, and mechanisms of accountability associated with the use of discretion by public officials. The law formally defines discretionary authority, outlines conditions for its application, and incorporates safeguards to ensure decisions align with legal norms and serve the public interest. The findings indicate that while the law improves legal certainty and promotes good governance, practical challenges remain in its application, including limited legal awareness among officials, fear of legal repercussions, and weak oversight mechanisms. The study concludes that strengthening institutional capacity and providing legal guidance are essential to ensure the responsible and effective use of discretion in public administration.